High-Resolution Time-Frequency Methods' Performance Analysis. (8th August 2010) - Shafi Shafi, Imran Imran; Ahmad Ahmad, Jamil Jamil; Shah Shah, Syed Ismail Syed Ismail; Ikram Ikram, Ataul Aziz Ataul Aziz; Ahmad Khan Ahmad Khan, Adnan Adnan; Bashir Bashir, Sajid Sajid; Kashif Kashif, Faisal Mahmood Faisal Mahmood
Abstract : This work evaluates the performance of high-resolution quadratic time-frequency distributions (TFDs) including the ones obtained by the reassignment method, the optimal radially Gaussian kernel method, the t-f autoregressive moving-average spectral estimation method and the neural network-based method. The approaches are rigorously compared to each other using several objective measures. Experimental results show that the neural network-based TFDs are better in concentration and resolution performance based on various examples.